Interhemispheric Asymmetries in Magnetosphere and Ionosphere Magnetic Field Residuals Between Swarm Observations and Earth Magnetic Field Models. Issue 3 (26th February 2022) - Shi, Yining; Moldwin, Mark B.
Abstract: We present a statistical study of magnetic field vector residual between Swarm observations and two Earth magnetic field models: the 13th generation International Geomagnetic Reference Field (IGRF) model and the CHAOS‐7 model. Statistics of these residuals are important for estimating potential errors for satellite operations when using Earth magnetic models as a reference, as well as for magnetosphere‐ionosphere‐thermosphere studies examining energy input into the system. Magnetic field residuals are calculated as vector differences between observations and model estimation at Swarm satellite positions from 2014 to 2020. Magnetic field residuals for both models increase as geomagnetic activity level increases, and the largest magnitude of vector difference can be around 1800 nT with relatively small angle differences. The CHAOS‐7 model shows lower magnetic field residuals compared to IGRF‐13. North‐south hemispheric asymmetries are seen in magnetic field residuals for high Kp values larger than 6 with the southern hemisphere (SH) having more frequent occurrence of magnetic field residuals larger than 300 nT, especially during SH summer. Most large residual values appear in the high‐latitude region with SH seeing additional large residuals around the South Atlantic Anomaly region. Midnight and noon sectors show the strongest interhemispheric asymmetries. The northern hemisphere shows more frequent occurrence of large residuals above 75° magnetic latitude throughout all local times compared to the SH. Identifying asymmetries in large magnetic residuals under high geomagnetic activity levels is helpful for studying the difference in response to ionospheric disturbances in the two hemispheres. Key Points: Comparison between Swarm magnetic field vector observations and Earth magnetic field models Statistical magnetic field residual maps show largest differences in high latitude region and around the South Atlantic Anomaly More frequent occurrence of large magnetic field residual under high geomagnetic activity levels in southern hemisphere